(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In this article on the material of Anna Bagriana’s plays transformational changes in writer’s works are demonstrated, as well as despite of existence in analyzed drama works of some elements of postmodern poetics, attempts are made to prove their belonging to a brandnew literary direction. Instead of postmodern deconstruction and perception of the world as chaos Anna Bagriana offers the reader a range of harmonizing principles, which are able to save a disappointed man of XXI century from the absurdity of life, the total loneliness and even the fear of death. Playwright resumes scale of human values, revives the historical memory, returns faith in the greatness of man, its kindness, sincerity, emphasizes the important role of the art and artists in the life of society.